Exhausted T cells hijacking the cancer-immunity cycle: Assets and liabilities - Brunell, Anna E.; Lahesmaa, Riitta; Autio, Anu; Thotakura, Anil K. (Frontiers in Immunology, 2023)
T cell exhaustion is an alternative differentiation path of T cells, sometimes described as a dysfunction. During the last decade, insights of T cell exhaustion acting as a bottle neck in the field of cancer immunotherapy have undoubtedly provoked attention. One of the main drivers of T cell exhaustion is persistent antigen stimulation, a prerequisite in the cancer-immunity cycle. The umbrella term “T cell exhaustion” comprises various stages of T cell functionalities, describing the dynamic, one-way exhaustion process. Together these qualities of T cells at the exhaustion continuum can enable tumor clearance, but if the exhaustion acquired timeframe is exceeded, tumor cells have increased possibilities of escaping immune system surveillance. This could be considered a tipping point where exhausted T cells switch from an asset to a liability. In this review, the contrary role of exhausted T cells is discussed.